A modified silica gel composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611219841.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]然而,硅橡胶在实际应用中也存在明显的性能缺陷
[0020]本发明通过改性聚硅氧烷与核壳结构耐热助剂的协同,显著提升了硅橡胶的热稳定性和阻燃性能。改性聚硅氧烷分子链中引入的邻碳硼烷笼状结构,在高温下优先氧化形成致密陶瓷化保护层,阻隔氧气扩散,延缓主链降解;刚性苯环侧基则限制硅氧烷链段的热重排,提高裂解活化能。侧链接枝的DOPO在燃烧时分解生成含磷活性物,催化基体表面形成致密膨胀炭层,其菲环结构进一步促进炭层石墨化,增强隔热隔氧效果。耐热助剂以掺铁氧化铈为核,利用Ce3+/Ce4+变价协同捕获热氧化自由基,从源头抑制老化;表面吸附的氮化硼纳米片凭借高导热性与二维片层阻隔效应,缓解热应力集中,延长氧气及热解气体扩散路径,提升抗热冲击能力;外层MIL-53(Al)高温热解转化为纳米多孔氧化铝,不仅物理吸附可燃挥发物,更作为交联节点与硅橡胶及氮化硼形成有机-无机杂化网络,强化高温流变下的结构抗塌性。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone rubber technology, specifically to a modified silicone composite material and its preparation method. Background Technology
[0002] Silicone rubber is a type of organic-inorganic hybrid polymer material with silicon-oxygen bonds as the main chain and organic groups as side chains. Due to its excellent high and low temperature resistance, electrical insulation, chemical stability, and weather resistance, silicone rubber has been widely used in many fields such as aerospace, electronics, automotive manufacturing, building sealing, wires and cables, and medical devices.
[0003] However, silicone rubber also has significant performance defects in practical applications. Regarding thermal stability, although silicone rubber can be used for extended periods below 200°C, its molecular chains undergo oxidation and cracking reactions at higher temperatures, leading to a sharp decline in mechanical properties and even loss of functionality. Studies have shown that high-temperature thermal aging causes an overall decrease in the mass and tensile strength of silicone rubber, while increasing its hardness and refractive index, severely impacting its long-term service reliability. In terms of flame retardancy, the numerous aliphatic alkyl structures on the side chains of silicone rubber make it easily ignited. Although a silica layer can form during combustion, its porous structure cannot effectively extinguish the flame. The inherent flammability of silicone rubber severely limits its application in situations requiring stringent flame retardancy.
[0004] Therefore, how to simultaneously improve the thermal stability and flame retardant properties of silicone rubber materials has become a key technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a modified silicone composite material that improves the thermal stability and flame retardant properties of silicone rubber.
[0006] The objective of this invention can be achieved through the following technical solutions: A method for preparing a modified silicone composite material specifically includes the following steps: Step S1: Put methyl vinyl silicone rubber into an open mixer and mix it in a triangular bag for 2 minutes at a roller temperature of 40-50℃. Then add fumed silica and mix for 20-30 minutes until the rubber compound becomes transparent. Then add heat-resistant additives and mix for 5 minutes. Then transfer it to a vacuum drying oven and heat treat it at a temperature of 110-120℃ for 2-3 hours to obtain the pretreated rubber compound. Step S2: Mix chloroplatinic acid and polydimethylsiloxane evenly to obtain a platinum catalyst. Add the pretreated rubber compound and modified polysiloxane to a mixer and mix for 10 minutes at a roller temperature of 35-40℃. Cool to room temperature and add the platinum catalyst. After mixing evenly, transfer to a mold and hot press for 20 minutes at a temperature of 60-70℃ to obtain the modified silicone composite material.
[0007] Furthermore, the weight ratio of methyl vinyl silicone rubber, fumed silica and heat-resistant additives in step S1 is 100-120:14-20:18-25, the methyl vinyl silicone rubber is type 110 silicone rubber with a relative molecular weight of 650,000 and a vinyl content of 0.16%.
[0008] Furthermore, in step S2, the ratio of chloroplatinic acid to polydimethyl vinyl silicone oil is 0.1g:10g, the weight ratio of pretreated adhesive, modified polysiloxane and platinum catalyst is 100-120:40-50:0.1-0.2, and the viscosity of polydimethyl vinyl silicone oil is 1000 Pa·s.
[0009] Furthermore, the modified polysiloxane is prepared by the following steps: Step A1: Mix diphenylo-carborane, tribromoisocyanuric acid and hexafluoroisopropanol evenly, stir and add trifluoromethanesulfonic acid at a speed of 200-300 r / min and a temperature of 30-35℃, and react for 1-2 h to obtain intermediate 1. Mix intermediate 1, palladium acetate, triphenylphosphine and xylene evenly, sonicate at a frequency of 30-40 kHz for 2-4 min, and then stir and add sodium bicarbonate and tetramethyltetravinylcyclotetrasiloxane at a speed of 200-300 r / min, a temperature of 110-120℃ and under nitrogen gas, and react for 20-24 h to obtain intermediate 2. Step A2: Mix intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and xylene evenly, and react for 8-10 h at a speed of 160-180 r / min, a temperature of 110-120 °C, and under nitrogen purging to obtain intermediate 3. Mix intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane and tetrahydrofuran evenly, and stir and add tetramethylammonium hydroxide at a speed of 200-300 r / min, a temperature of 80-100 °C, and under nitrogen purging to obtain modified polysiloxane.
[0010] Furthermore, the ratio of diphenylo-borane, tribromoisocyanuric acid, hexafluoroisopropanol, and trifluoromethanesulfonic acid used in step A1 is 0.75g:0.98g:50mL:0.25mL, and the ratio of intermediate 1, palladium acetate, triphenylphosphine, xylene, sodium bicarbonate, and tetramethyltetravinylcyclotetrasiloxane used is 1mmol:0.04mmol:0.36mmol:10mL:1.02g:0.2g.
[0011] Furthermore, in step A2, the ratio of intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene is 1 mmol:4.2 mmol:15 mL, and the ratio of intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, tetrahydrofuran, tetramethylammonium hydroxide, and hexamethyldisiloxane is 0.8-1 mmol:1 mmol:12 mL:0.03 mmol:0.1 mmol.
[0012] Furthermore, the heat-resistant additive is prepared by the following steps: Step B1: Cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, and deionized water are dispersed in ethylene glycol and stirred for 30-40 minutes at a speed of 180-200 r / min and a temperature of 20-30℃. Then, the mixture is heated at a temperature of 170-180℃ for 6-8 hours, cooled to room temperature, centrifuged, and dried. Finally, the mixture is calcined at a temperature of 320-350℃ for 1 hour to obtain the pretreatment aid. Step B2: Disperse the pretreatment aid in Tris buffer at pH 8.5, sonicate at a frequency of 30-40 kHz for 40-50 min, then stir and add dopamine hydrochloride at a speed of 450-500 r / min and a temperature of 40-50 ℃, and react for 4-6 h to obtain the pretreatment aid. Step B3: Disperse boron nitride nanosheets in ethanol and ultrasonically exfoliate them for 1-2 hours at a frequency of 40-60 kHz to obtain a stable suspension. Mix the suspension and pretreatment agent evenly and stir for 2-4 hours at a speed of 300-400 r / min to obtain the modified agent. Step B4: Mix the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide evenly, and sonicate at a frequency of 30-40kHz for 20-30 minutes. Then, react at a speed of 200-300r / min and a temperature of 110-120℃ for 20-24 hours. After centrifugation and washing, vacuum dry at a temperature of 80℃ to obtain the heat-resistant additive.
[0013] Furthermore, in step B1, the ratio of cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, deionized water, and ethylene glycol is 4g:1.6g:0.5g:4.5mL:120mL. The polyvinylpyrrolidone is brand K29-32 with an average molecular weight of approximately 58,000.
[0014] Furthermore, the ratio of the pretreatment aid, Tris buffer, and dopamine hydrochloride mentioned in step B2 is 2g:100mL:0.8g.
[0015] Furthermore, in step B3, the ratio of boron nitride nanosheets to ethanol is 0.15-0.2g:120mL, and the ratio of suspension to pretreatment aid is 120mL:2.1g.
[0016] Furthermore, the ratio of the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water, and N,N-dimethylformamide mentioned in step B4 is 150-200 mg: 80 mg: 50-55 mg: 10 mL: 10 mL.
[0017] The beneficial effects of this invention are as follows: This process consists of two stages: pretreatment and vulcanization. In the pretreatment stage, methyl vinyl silicone rubber, silica, and heat-resistant additives are mixed and subjected to high-temperature vacuum heat treatment, which promotes the condensation of silanol groups on the surface of silica with the rubber chains, achieving chemical reinforcement and eliminating structural defects. In the vulcanization stage, platinum complex catalysis causes hydrosilylation between the pretreated rubber particles and the modified polysiloxane, constructing a three-dimensional cross-linked network, ultimately yielding the modified silicone composite material.
[0018] Modified polysiloxanes: Using trifluoromethanesulfonic acid as a catalyst and tribromoisocyanuric acid as a mild bromide cation donor, electrophilic bromination was performed on the B(9 / 12) position of the diphenylo-borane cage, far from the carbon atom, to prepare an active intermediate 1 containing a B-Br bond. Using a palladium acetate / triphenylphosphine system as a zero-valent palladium catalyst precursor, a Heck-type coupling reaction was catalyzed between the B-Br bond on intermediate 1 and the vinyl group on tetramethyltetravinylcyclotetrasiloxane to prepare intermediate 2. 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide contains an active PH bond; under heating conditions, the phosphorus atom acts as a nucleophilic center to attack the electron-rich vinyl group, yielding intermediate 3. Tetramethylammonium hydroxide was used as a basic catalyst to initiate anionic ring-opening polymerization of intermediate 3 with 2,4,6,8-tetramethylcyclotetrasiloxane. The reaction opens the siloxane ring through nucleophilic attack, forming an active chain end, achieving linear polymer chain growth, and finally terminating the reaction by hexamethyldisiloxane end-capping to obtain modified polysiloxane.
[0019] Heat-resistant additives: Utilizing the weak reducing properties and high boiling point of ethylene glycol, Ce is induced in a solvothermal system. 3+ and Fe 3+Co-hydrolysis and condensation form a cerium-iron composite hydroxide precursor. Simultaneously, polyvinylpyrrolidone (PVP) acts as a surfactant, effectively preventing particle aggregation. High-temperature baking then removes the PVP organic framework and water of crystallization, promoting the transformation of the precursor into a highly crystalline heterojunction oxide (CeO2-Fe2O3), which is the pretreatment aid. Under a weakly alkaline aerobic environment, dopamine hydrochloride is dehydrochlorinated and oxidized to dopaquinone, further undergoing intramolecular cyclization, rearrangement, and covalent cross-linking, ultimately forming a dense polydopamine coating layer on the surface of the pretreatment aid, thus obtaining the pretreatment aid. The aromatic ring structure on the polydopamine molecule generates a strong π-π stacking interaction with the hexagonal lattice of boron nitride nanosheets, while its polar groups form hydrogen bonds with the hydroxyl / amino groups at the nanosheet edges. Through this strong non-covalent anchoring effect, boron nitride nanosheets are tightly composited on the surface of the pretreatment aid, yielding a modified aid. Under solvothermal conditions, Al... 3+ It undergoes a coordination reaction with terephthalic acid to form the MIL-53(Al) metal-organic framework. The polydopamine on the surface of the modifier is rich in -OH and -NH2 active sites, which can effectively chelate Al. 3+ It also induces in-situ heterogeneous nucleation and growth of metal-organic frameworks on its surface to obtain heat-resistant additives.
[0020] This invention significantly improves the thermal stability and flame retardant properties of silicone rubber through the synergistic effect of modified polysiloxane and core-shell structured heat-resistant additives. The ortho-carborane cage structure introduced into the modified polysiloxane molecular chain preferentially oxidizes at high temperatures to form a dense ceramic protective layer, blocking oxygen diffusion and delaying main chain degradation; the rigid benzene ring side groups restrict the thermal rearrangement of siloxane segments, increasing the pyrolysis activation energy. The DOPO branched on the side links decomposes during combustion to generate phosphorus-containing active substances, catalyzing the formation of a dense, expanded carbon layer on the matrix surface. Its phenanthrene ring structure further promotes the graphitization of the carbon layer, enhancing the heat insulation and oxygen barrier effects. The heat-resistant additive uses iron-doped cerium oxide as the core, utilizing Ce... 3+ / Ce 4+ The variable valence synergistic capture of thermally oxidized free radicals inhibits aging at its source; the boron nitride nanosheets adsorbed on the surface alleviate thermal stress concentration, prolong the diffusion path of oxygen and pyrolysis gases, and enhance thermal shock resistance due to their high thermal conductivity and two-dimensional sheet barrier effect; the outer layer of MIL-53(Al) is transformed into nanoporous alumina through high-temperature pyrolysis, which not only physically adsorbs combustible volatiles, but also acts as a crosslinking node to form an organic-inorganic hybrid network with silicone rubber and boron nitride, thereby strengthening the structural resistance to collapse under high-temperature rheological conditions. Detailed Implementation
[0021] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1: A method for preparing a modified silicone composite material, specifically including the following steps: Step S1: Put methyl vinyl silicone rubber into an open mixing mill and mix it in a triangular bag for 2 minutes at a roller temperature of 40°C. Then add fumed silica and mix for 20 minutes until the rubber compound becomes transparent. Then add heat-resistant additives and mix for 5 minutes. Then transfer it to a vacuum drying oven and heat treat it at a temperature of 110°C for 2 hours to obtain the pretreated rubber compound. Step S2: Mix chloroplatinic acid and polydimethylsiloxane evenly to obtain a platinum catalyst. Add the pretreated rubber compound and modified polysiloxane to a mixer and mix for 10 minutes at a roller temperature of 35°C. Cool to room temperature and add the platinum catalyst. After mixing evenly, transfer to a mold and hot press at a temperature of 60°C for 20 minutes to obtain a modified silicone composite material.
[0023] The weight ratio of methyl vinyl silicone rubber, fumed silica and heat-resistant additives in step S1 is 120:14:18. The methyl vinyl silicone rubber is type 110 silicone rubber with a relative molecular weight of 650,000 and a vinyl content of 0.16%.
[0024] The ratio of chloroplatinic acid to polydimethyl vinyl silicone oil in step S2 is 0.1g:10g, the weight ratio of pretreated adhesive, modified polysiloxane and platinum catalyst is 120:40:0.1, and the viscosity of polydimethyl vinyl silicone oil is 1000 Pa·s.
[0025] The modified polysiloxane is prepared by the following steps: Step A1: Diphenyl-o-carborane, tribromoisocyanuric acid and hexafluoroisopropanol were mixed evenly and stirred at 200 r / min and 30 °C, and trifluoromethanesulfonic acid was added. The mixture was reacted for 1 h to obtain intermediate 1. Intermediate 1, palladium acetate, triphenylphosphine and xylene were mixed evenly and ultrasonically treated at 30 kHz for 2 min. Then, sodium bicarbonate and tetramethyltetravinylcyclotetrasiloxane were added at 200 r / min and 110 °C under nitrogen gas and stirred for 20 h to obtain intermediate 2. Step A2: Intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and xylene are mixed evenly and reacted for 8 hours at a speed of 160 r / min, a temperature of 110 °C and under nitrogen purging to obtain intermediate 3. Intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane and tetrahydrofuran are mixed evenly and reacted for 2 hours at a speed of 200 r / min, a temperature of 80 °C and under nitrogen purging to obtain modified polysiloxane.
[0026] The ratio of diphenylo-carborane, tribromoisocyanuric acid, hexafluoroisopropanol, and trifluoromethanesulfonic acid used in step A1 is 0.75g:0.98g:50mL:0.25mL. The ratio of intermediate 1, palladium acetate, triphenylphosphine, xylene, sodium bicarbonate, and tetramethyltetravinylcyclotetrasiloxane used is 1mmol:0.04mmol:0.36mmol:10mL:1.02g:0.2g.
[0027] The ratio of intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene in step A2 is 1 mmol:4.2 mmol:15 mL, and the ratio of intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, tetrahydrofuran, tetramethylammonium hydroxide, and hexamethyldisiloxane is 0.8 mmol:1 mmol:12 mL:0.03 mmol:0.1 mmol.
[0028] The heat-resistant additive is prepared by the following steps: Step B1: Cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate and deionized water are dispersed in ethylene glycol and stirred for 30 min at 180 r / min and 20 °C. Then, the mixture is heated at 170 °C for 6 h, cooled to room temperature, centrifuged and dried. Finally, it is calcined at 320 °C for 1 h to obtain the pretreatment aid. Step B2: Disperse the pretreatment agent in Tris buffer at pH 8.5, sonicate at 30 kHz for 40 min, then stir and add dopamine hydrochloride at 450 r / min and 40 ℃, and react for 4 h to obtain the pretreatment agent. Step B3: Disperse boron nitride nanosheets in ethanol and ultrasonically exfoliate them for 1 hour at a frequency of 40 kHz to obtain a stable suspension. Mix the suspension and pretreatment agent evenly and stir for 2 hours at a speed of 300 r / min to obtain the modified agent. Step B4: Mix the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide evenly, sonicate at 30kHz for 20min, then react at 200r / min and 110℃ for 20h. After centrifugation and washing, vacuum dry at 80℃ to obtain the heat-resistant additive.
[0029] The ratio of cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, deionized water, and ethylene glycol in step B1 is 4g:1.6g:0.5g:4.5mL:120mL. The polyvinylpyrrolidone is brand K29-32 with an average molecular weight of approximately 58,000.
[0030] The ratio of the pretreatment aid, Tris buffer, and dopamine hydrochloride mentioned in step B2 is 2g:100mL:0.8g.
[0031] In step B3, the ratio of boron nitride nanosheets to ethanol is 0.15 g: 120 mL, and the ratio of suspension to pretreatment aid is 120 mL: 2.1 g.
[0032] The ratio of the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water, and N,N-dimethylformamide mentioned in step B4 is 150mg:80mg:50mg:10mL:10mL.
[0033] Example 2, a method for preparing a modified silicone composite material, specifically includes the following steps: Step S1: Put methyl vinyl silicone rubber into an open mixing mill and mix it in a triangular bag for 2 minutes at a roller temperature of 45°C. Then add fumed silica and mix for 25 minutes until the rubber compound becomes transparent. Then add heat-resistant additives and mix for 5 minutes. Then transfer it to a vacuum drying oven and heat treat it at a temperature of 115°C for 2 hours to obtain the pretreated rubber compound. Step S2: Mix chloroplatinic acid and polydimethylsiloxane evenly to obtain a platinum catalyst. Add the pretreated rubber compound and modified polysiloxane to a mixer and mix for 10 minutes at a roller temperature of 35°C. Cool to room temperature and add the platinum catalyst. After mixing evenly, transfer to a mold and hot press at a temperature of 65°C for 20 minutes to obtain the modified silicone composite material.
[0034] The weight ratio of methyl vinyl silicone rubber, fumed silica and heat-resistant additives in step S1 is 120:14:21. The methyl vinyl silicone rubber is type 110 silicone rubber with a relative molecular weight of 650,000 and a vinyl content of 0.16%.
[0035] The ratio of chloroplatinic acid to polydimethyl vinyl silicone oil in step S2 is 0.1g:10g, the weight ratio of pretreated adhesive, modified polysiloxane and platinum catalyst is 120:45:0.1, and the viscosity of polydimethyl vinyl silicone oil is 1000 Pa·s.
[0036] The modified polysiloxane is prepared by the following steps: Step A1: Diphenyl o-carborane, tribromoisocyanuric acid and hexafluoroisopropanol were mixed evenly and stirred at 250 r / min and 32 °C, and trifluoromethanesulfonic acid was added. The mixture was reacted for 1 h to obtain intermediate 1. Intermediate 1, palladium acetate, triphenylphosphine and xylene were mixed evenly and ultrasonically treated at 35 kHz for 3 min. Then, sodium bicarbonate and tetramethyltetravinylcyclotetrasiloxane were added at 250 r / min and 115 °C under nitrogen gas and stirred for 22 h to obtain intermediate 2. Step A2: Intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene are mixed evenly and reacted for 9 hours at a speed of 170 r / min, a temperature of 115 °C, and under nitrogen purging to obtain intermediate 3. Intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, and tetrahydrofuran are mixed evenly and reacted for 3 hours at a speed of 250 r / min, a temperature of 90 °C, and under nitrogen purging to obtain modified polysiloxane.
[0037] The ratio of diphenylo-carborane, tribromoisocyanuric acid, hexafluoroisopropanol, and trifluoromethanesulfonic acid used in step A1 is 0.75g:0.98g:50mL:0.25mL. The ratio of intermediate 1, palladium acetate, triphenylphosphine, xylene, sodium bicarbonate, and tetramethyltetravinylcyclotetrasiloxane used is 1mmol:0.04mmol:0.36mmol:10mL:1.02g:0.2g.
[0038] The ratio of intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene in step A2 is 1 mmol:4.2 mmol:15 mL, and the ratio of intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, tetrahydrofuran, tetramethylammonium hydroxide, and hexamethyldisiloxane is 0.8 mmol:1 mmol:12 mL:0.03 mmol:0.1 mmol.
[0039] The heat-resistant additive is prepared by the following steps: Step B1: Cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate and deionized water are dispersed in ethylene glycol and stirred for 35 min at 190 r / min and 25 °C. Then, the mixture is heated at 175 °C for 7 h, cooled to room temperature, centrifuged and dried. Finally, it is calcined at 340 °C for 1 h to obtain the pretreatment aid. Step B2: Disperse the pretreatment aid in Tris buffer at pH 8.5, sonicate at 35 kHz for 45 min, then stir and add dopamine hydrochloride at 470 r / min and 45 ℃, and react for 5 h to obtain the pretreatment aid. Step B3: Disperse boron nitride nanosheets in ethanol and ultrasonically exfoliate them for 1 hour at a frequency of 50 kHz to obtain a stable suspension. Mix the suspension and pretreatment agent evenly and stir for 3 hours at a speed of 350 r / min to obtain the modified agent. Step B4: Mix the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide evenly, sonicate at 35kHz for 25min, then react at 250r / min and 115℃ for 22h. After centrifugation and washing, vacuum dry at 80℃ to obtain the heat-resistant additive.
[0040] The ratio of cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, deionized water, and ethylene glycol in step B1 is 4g:1.6g:0.5g:4.5mL:120mL. The polyvinylpyrrolidone is brand K29-32 with an average molecular weight of approximately 58,000.
[0041] The ratio of the pretreatment aid, Tris buffer, and dopamine hydrochloride mentioned in step B2 is 2g:100mL:0.8g.
[0042] In step B3, the ratio of boron nitride nanosheets to ethanol is 0.15 g: 120 mL, and the ratio of suspension to pretreatment aid is 120 mL: 2.1 g.
[0043] The ratio of the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water, and N,N-dimethylformamide mentioned in step B4 is 60mg:80mg:50mg:10mL:10mL.
[0044] Example 3, a method for preparing a modified silicone composite material, specifically includes the following steps: Step S1: Put methyl vinyl silicone rubber into an open mixing mill and mix it in a triangular bag for 2 minutes at a roller temperature of 50°C. Then add fumed silica and mix for 30 minutes until the rubber compound becomes transparent. Then add heat-resistant additives and mix for 5 minutes. Then transfer it to a vacuum drying oven and heat treat it at a temperature of 120°C for 3 hours to obtain the pretreated rubber compound. Step S2: Mix chloroplatinic acid and polydimethylsiloxane evenly to obtain a platinum catalyst. Add the pretreated rubber compound and modified polysiloxane to a mixer and mix for 10 minutes at a roller temperature of 40°C. Cool to room temperature and add the platinum catalyst. After mixing evenly, transfer to a mold and hot press at a temperature of 70°C for 20 minutes to obtain a modified silicone composite material.
[0045] The weight ratio of methyl vinyl silicone rubber, fumed silica and heat-resistant additives in step S1 is 120:14:25. The methyl vinyl silicone rubber is type 110 silicone rubber with a relative molecular weight of 650,000 and a vinyl content of 0.16%.
[0046] The ratio of chloroplatinic acid to polydimethyl vinyl silicone oil in step S2 is 0.1g:10g, the weight ratio of pretreated adhesive, modified polysiloxane and platinum catalyst is 120:50:0.1, and the viscosity of polydimethyl vinyl silicone oil is 1000 Pa·s.
[0047] The modified polysiloxane is prepared by the following steps: Step A1: Diphenylo-carborane, tribromoisocyanuric acid and hexafluoroisopropanol were mixed evenly and stirred at 300 r / min and 35°C, and trifluoromethanesulfonic acid was added. The mixture was reacted for 2 h to obtain intermediate 1. Intermediate 1, palladium acetate, triphenylphosphine and xylene were mixed evenly and ultrasonically treated at 40 kHz for 4 min. Then, sodium bicarbonate and tetramethyltetravinylcyclotetrasiloxane were added at 300 r / min and 120°C under nitrogen gas and stirred for 24 h to obtain intermediate 2. Step A2: Intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and xylene are mixed evenly and reacted for 10 h at a speed of 180 r / min, a temperature of 120 °C and a nitrogen atmosphere to obtain intermediate 3. Intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane and tetrahydrofuran are mixed evenly and reacted for 4 h at a speed of 300 r / min, a temperature of 100 °C and a nitrogen atmosphere to obtain modified polysiloxane.
[0048] The ratio of diphenylo-carborane, tribromoisocyanuric acid, hexafluoroisopropanol, and trifluoromethanesulfonic acid used in step A1 is 0.75g:0.98g:50mL:0.25mL. The ratio of intermediate 1, palladium acetate, triphenylphosphine, xylene, sodium bicarbonate, and tetramethyltetravinylcyclotetrasiloxane used is 1mmol:0.04mmol:0.36mmol:10mL:1.02g:0.2g.
[0049] The ratio of intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene in step A2 is 1 mmol:4.2 mmol:15 mL, and the ratio of intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, tetrahydrofuran, tetramethylammonium hydroxide, and hexamethyldisiloxane is 0.8 mmol:1 mmol:12 mL:0.03 mmol:0.1 mmol.
[0050] The heat-resistant additive is prepared by the following steps: Step B1: Cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate and deionized water are dispersed in ethylene glycol and stirred for 40 min at 200 r / min and 30 °C. Then, the mixture is heated at 180 °C for 8 h, cooled to room temperature, centrifuged and dried. Finally, it is calcined at 350 °C for 1 h to obtain the pretreatment aid. Step B2: Disperse the pretreatment aid in Tris buffer at pH 8.5, sonicate at 40 kHz for 50 min, then stir and add dopamine hydrochloride at 50 ℃ for 6 h to obtain the pretreatment aid. Step B3: Disperse boron nitride nanosheets in ethanol and ultrasonically exfoliate them for 2 hours at a frequency of 60 kHz to obtain a stable suspension. Mix the suspension and pretreatment agent evenly and stir for 4 hours at a speed of 400 r / min to obtain the modified agent. Step B4: Mix the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide evenly, sonicate at 40kHz for 30min, then react at 300r / min and 120℃ for 24h. After centrifugation and washing, vacuum dry at 80℃ to obtain the heat-resistant additive.
[0051] The ratio of cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, deionized water, and ethylene glycol in step B1 is 4g:1.6g:0.5g:4.5mL:120mL. The polyvinylpyrrolidone is brand K29-32 with an average molecular weight of approximately 58,000.
[0052] The ratio of the pretreatment aid, Tris buffer, and dopamine hydrochloride mentioned in step B2 is 2g:100mL:0.8g.
[0053] In step B3, the ratio of boron nitride nanosheets to ethanol is 0.15 g: 120 mL, and the ratio of suspension to pretreatment aid is 120 mL: 2.1 g.
[0054] The ratio of the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water, and N,N-dimethylformamide mentioned in step B4 is 150mg:80mg:55mg:10mL:10mL.
[0055] Comparative Example 1: Compared with Example 1, this comparative example uses tetramethyltetravinylcyclotetrasiloxane instead of intermediate 2, and the remaining steps are the same.
[0056] Comparative Example 2: In this comparative example, compared with Example 1, intermediate 2 was hydrogenated by palladium catalyst on carbon, and then intermediate 3 was replaced. The remaining steps were the same.
[0057] Comparative Example 3: This comparative example uses a pretreatment agent instead of a modifying agent, while the other steps are the same as in Example 1.
[0058] Comparative Example 4: This comparative example uses a modified additive instead of a heat-resistant additive, while the other steps are the same as in Example 1.
[0059] According to GB / T 528-2009 "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber", the modified silicone composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were cut into type 1A dumbbell-shaped specimens. After conditioning in a standard laboratory environment, their tensile strength and elongation at break were measured. Then, the same batch of specimens were subjected to accelerated aging and heat resistance testing in hot air according to Method B of GB / T 3512-2014 "Accelerated Aging and Heat Resistance Test of Vulcanized Rubber or Thermoplastic Rubber", suspended in a forced-air drying oven and aged at 350℃ for 48 hours. The tensile strength and elongation at break of the aged specimens were measured. Five parallel samples were tested for each group of specimens, and the average value was taken. Based on the test data before and after aging, the tensile strength retention rate and elongation at break retention rate were calculated respectively. The test results are shown in Table 1.
[0060] The modified silicone composite materials prepared in Examples 1-3 and Comparative Examples 1-4 were tested according to Method B of GB / T 10707-2008 "Determination of the Burning Performance of Rubber" using the vertical burning method. The sample was a strip-shaped sample with a length of 130 mm, a width of 13 mm, and a thickness of 3 mm. The flaming time of each sample after each application of flame was recorded. The test results are shown in Table 1.
[0061]
[0062] As shown in Table 1, the modified silicone composite materials prepared in Examples 1-3, after aging at 350℃ for 48 hours, retained tensile strength in the range of 82.6-86.2% and elongation at break in the range of 88.3-91.5%, while meeting the requirements of FV-0 vertical burning performance. This indicates that the silicone rubber of the present invention has good thermal stability and flame retardant properties.
[0063] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a modified silicone composite material, characterized in that: Specifically, the steps include the following: Step S1: Put methyl vinyl silicone rubber into an open mixing mill, mix it in a triangular bag, then add fumed silica and mix until the rubber compound becomes transparent. Then add heat-resistant additives, mix it, and then transfer it to a vacuum drying oven for heat treatment for a period of time to obtain the pretreated rubber compound. Step S2: Chloroplatinic acid and polydimethylsiloxane are mixed evenly to obtain a platinum catalyst. The pretreated rubber compound and modified polysiloxane are added to a mixer for mixing. After cooling to room temperature, the platinum catalyst is added and mixed evenly. The mixture is then transferred to a mold for hot pressing to obtain a modified silicone composite material. The weight ratio of methyl vinyl silicone rubber, fumed silica and heat-resistant additives in step S1 is 100-120:14-20:18-25; In step S2, the ratio of chloroplatinic acid to polydimethylsiloxane is 0.1g:10g, and the weight ratio of pretreated adhesive, modified polysiloxane, and platinum catalyst is 100-120:40-50:0.1-0.
2.
2. The method for preparing a modified silicone composite material according to claim 1, characterized in that: The modified polysiloxane is prepared by the following steps: Step A1: Mix diphenylo-carborane, tribromoisocyanuric acid and hexafluoroisopropanol evenly, stir and add trifluoromethanesulfonic acid to react and obtain intermediate 1. Mix intermediate 1, palladium acetate, triphenylphosphine and xylene evenly, sonicate, then stir and add sodium bicarbonate and tetramethyltetravinylcyclotetrasiloxane to react and obtain intermediate 2. Step A2: Intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and xylene are mixed evenly and reacted to obtain intermediate 3. Intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane and tetrahydrofuran are mixed evenly, stirred and tetramethylammonium hydroxide is added and reacted. Then hexamethyldisiloxane is added and reacted to obtain modified polysiloxane.
3. The method for preparing a modified silicone composite material according to claim 2, characterized in that: The ratio of diphenylo-carborane, tribromoisocyanuric acid, hexafluoroisopropanol, and trifluoromethanesulfonic acid used in step A1 is 0.75g:0.98g:50mL:0.25mL. The ratio of intermediate 1, palladium acetate, triphenylphosphine, xylene, sodium bicarbonate, and tetramethyltetravinylcyclotetrasiloxane used is 1mmol:0.04mmol:0.36mmol:10mL:1.02g:0.2g.
4. The method for preparing a modified silicone composite material according to claim 2, characterized in that: The ratio of intermediate 2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and xylene in step A2 is 1 mmol:4.2 mmol:15 mL, and the ratio of intermediate 3, 2,4,6,8-tetramethylcyclotetrasiloxane, tetrahydrofuran, tetramethylammonium hydroxide, and hexamethyldisiloxane is 0.8-1 mmol:1 mmol:12 mL:0.03 mmol:0.1 mmol.
5. The method for preparing a modified silicone composite material according to claim 1, characterized in that: The heat-resistant additive is prepared by the following steps: Step B1: Cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate and deionized water are dispersed in ethylene glycol, stirred, heated, cooled to room temperature, centrifuged, dried, and finally calcined to obtain the pretreatment aid. Step B2: Disperse the pretreatment aid in Tris buffer, sonicate, then stir and add dopamine hydrochloride to react and obtain the pretreatment aid; Step B3: Disperse boron nitride nanosheets in ethanol, exfoliate them by ultrasonication to obtain a stable suspension, mix the suspension and pretreatment agent evenly, and stir to obtain the modified agent. Step B4: Mix the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide evenly, sonicate, react, centrifuge, wash and then vacuum dry to obtain the heat-resistant additive.
6. The method for preparing a modified silicone composite material according to claim 5, characterized in that: The ratio of cerium nitrate hexahydrate, polyvinylpyrrolidone, ferric chloride hexahydrate, deionized water, and ethylene glycol used in step B1 is 4g:1.6g:0.5g:4.5mL:120mL.
7. The method for preparing a modified silicone composite material according to claim 5, characterized in that: The ratio of the pretreatment aid, Tris buffer, and dopamine hydrochloride mentioned in step B2 is 2g:100mL:0.8g.
8. The method for preparing a modified silicone composite material according to claim 5, characterized in that: In step B3, the ratio of boron nitride nanosheets to ethanol is 0.15-0.2g:120mL, and the ratio of suspension to pretreatment aid is 120mL:2.1g.
9. The method for preparing a modified silicone composite material according to claim 5, characterized in that: The ratio of the modified additive, aluminum nitrate nonahydrate, terephthalic acid, deionized water and N,N-dimethylformamide mentioned in step B4 is 150-200mg:80mg:50-55mg:10mL:10mL.
10. A modified silicone composite material, characterized in that: Prepared according to any one of the preparation methods described in claims 1-9.